The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1139/g11-018
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity studies inPhaseolusspecies by DNA barcoding

Abstract: The potential of DNA barcoding was tested as a system for studying genetic diversity and genetic traceability in bean germplasm. This technique was applied to several pure lines of Phaseolus vulgaris L. belonging to wild, domesticated, and cultivated common beans, along with some accessions of Phaseolus coccineus L., Phaseolus lunatus L., and Vigna unguiculata (L.) Walp. A multilocus approach was exploited using three chloroplast genic regions (rbcL, trnL, and matK), four intergenic spacers (rpoB-trnC, atpBrbc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…In particular, the DNA genotyping method applied in this research allowed us to identify the landraces that most likely represent the historical gene pool of common buckwheat cultivated in Valtellina among different local accessions and foreign materials. Other studies reported that different molecular techniques can be used for characterization of the landraces and investigation on their origin, like DNA barcoding (Nicolè et al 2011) and DNA fingerprinting (Gwanama et al 2000;Ferriol et al 2004). In general, these tools are of special interest because they provide basic information useful, if not essential, for the preservation and valorization (even commercial) of abandoned landraces.…”
Section: Implications For the Identification Of Local Alpine F Esculmentioning
confidence: 99%
“…In particular, the DNA genotyping method applied in this research allowed us to identify the landraces that most likely represent the historical gene pool of common buckwheat cultivated in Valtellina among different local accessions and foreign materials. Other studies reported that different molecular techniques can be used for characterization of the landraces and investigation on their origin, like DNA barcoding (Nicolè et al 2011) and DNA fingerprinting (Gwanama et al 2000;Ferriol et al 2004). In general, these tools are of special interest because they provide basic information useful, if not essential, for the preservation and valorization (even commercial) of abandoned landraces.…”
Section: Implications For the Identification Of Local Alpine F Esculmentioning
confidence: 99%
“…There are many advantages in the use of DNA barcoding as it is reproducible and testable as long as the link between DNA test sequences and reference specimens is supported, and also verifiable at any time and by any researcher [4]. Moreover, the experimental procedure for extracting genomic DNA and amplifying specific DNA markers is technically easy and usually does not require the destruction of the sample, which sometimes is valuable and therefore needs to be safeguarded [6].…”
Section: Discussionmentioning
confidence: 99%
“…Of the protein-coding genes present on the animal mitochondrial genome, the use of cytochrome c oxidase subunit 1 (cox1 or COI) was proposed as a standard barcode marker for animal species for two main reasons: universal primers make a 648 bp fragment at the 5 1 end of this gene easy to amplify in a broad spectrum of phyla, and its nucleotide substitution rate allows not only closely related species to be distinguished but, in some taxa, also different populations, biotypes or races of the same species. Other mitochondrial genes were suggested as barcode markers, including cob, which encodes for apocytochrome b; cox2 and cox3, which encode for the cytochrome oxidase subunits 2 and 3, respectively; nad1, which encodes for NADH dehydrogenase subunit 1; and the mitochondrial 16S-rDNA gene ( [4][5][6] and references therein).…”
Section: Rationale On Dna Barcoding As a Molecular Assay For Species mentioning
confidence: 99%
See 1 more Smart Citation
“…The employment of DNA barcoding at the sub-species level, instead, is not a conventional application of the methodology. Consequently, this research aims to assess the applicability of chloroplast DNA barcoding to unambiguously distinguish varietal genotypes of V. vinifera [21]. Since the genetic distance among subgroups within a species is generally too small to allow the definition of a genetic threshold to delimitate different varieties, a character-state DNA sequencing procedure based on single-copy nuclear genes was also developed [22].…”
Section: Introductionmentioning
confidence: 99%